Three fetuses karyotyped as Turner syndrome with cystic hygroma developing hydrops: prognosis and outcome - (:unkn) unknown (I R O G CANADA, INC, 2007)
Introduction: We present three cases of fetuses diagnosed as Turner syndrome with cystic hygroma (CH) developing hydrops to discuss the prenatal diagnostic and prognostic criteria of CH in ultrasound and outcome of the fetuses. Cases: The first case was 30-year-old pregnant woman with a nuchal translucency measurement of 8 mm at 12 weeks' gestation. Serial ultrasound examinations revealed non-septated cystic hygroma and hydrops. The pregnancy was terminated at the 18(th) week of gestation. Diagnosis of CH was made at 14 and 15 weeks of gestation in case 2 and case 3, respectively. Ultrasound revealed large cystic septated sacs in the nuchal area combined with serosal fluid collection and cutaneous edema. Spontaneous fetal demise occured at 21 and 16 weeks of gestation in cases 2 and 3, respectively. All fetuses were diagnosed as Turner syndrome.
Keywords: cystic hygroma; turner syndrome; hydrops fetalis; outcome; PRENATAL-DIAGNOSIS; NATURAL-HISTORY; COLLI